Harmonious technology a Confucian ethics of technology - Wong, Pak Hang 1980-; Wang, Tom Xiaowei (Routledge, 2021)
Technology has become a major subject of philosophical ethical reflection in recent years, as the novelty and disruptiveness of technology confront us with new possibilities and unprecedented outcomes as well as fundamental changes to our "normal" ways of living that demand deep reflection of technology. However, philosophical and ethical analysis of technology has until recently drawn primarily from the Western philosophical and ethical traditions, and philosophers and scholars of technology discuss the potential contribution of non-Western approaches only sparingly. Given the global nature of technology, however, there is an urgent need for multiculturalism in philosophy and ethics of technology that include non-Western perspectives in our thinking about technology. While there is an increased attention to non-Western philosophy in the field, there are few systematic attempts to articulate different approaches to the ethics of technology based on other philosophical and ethical traditions. The present edited volume picks up the task of diversifying the ethics of technology by exploring the possibility of Confucian ethics of technology. In the six chapters of this volume, the authors examine various ideas, concepts, and theories in Confucianism and apply them to the ethical challenges of technology; in the epilogue, the editors review the key ideas articulated throughout the volume to identify possible ways forward for Confucian ethics of technology. Harmonious Technology revives Confucianism for philosophical and ethical analysis of technology and presents Confucian ethics of technology as another approach to the ethics of technology. It will be essential for philosophers and ethicists of technology, who are urged to consider beyond the Western paradigms. More broadly, the volume will be of interest to students and scholars in the fields of philosophy, science and technology studies, innovation studies, political science, and social studies